The Technical Foundations of the Theory of Termination - Attia Al-Shammari, Ahmed Neama (Technium Education and Humanities, 2026)
Praise be to God, and peace and blessings be upon the Chosen Prophet, his family, his companions, and all those who follow his path. O God, show us the truth as it is and grant us the ability to follow it, and show us falsehood as it is and grant us the ability to avoid it. Now then: First and foremost, the fundamental principle in contracts is their binding nature, as stated in the Almighty’s words: "O you who have believed, fulfill your contracts"(1). The intended purpose of fulfilling a contract is its execution in a manner consistent with the principle of good faith in contract execution (2). Good faith presupposes that the clauses contained in the contract must be implemented. The binding nature of execution is not limited to one party to the contract alone, but extends to all parties. Therefore, the concept of reciprocity in obligations paves the way for the application of the principle of fulfilling contractual clauses. Furthermore, this situation is not permanent, but rather fluctuates with the circumstances of contract execution, sometimes favorable and sometimes unfavorable. The law permits a contracting party to be released from the contractual obligation if the other party’s performance becomes impossible. This simultaneously represents the penalty for breaching contractual obligations(3). This outcome undoubtedly indicates the extent of respect and sanctity accorded to the contractual bond, and also points to the concept of the penalty resulting from disrespecting this bond. The obligations, however, while placing the option of termination in the hands of the contracting party, signify the independence of that party in releasing themselves from contractual obligations. It places the fate of the entire contract under the authority of one of the parties, as termination serves as a penalty, holding the defaulting party liable. On the other hand, it represents the non-liability of the party exercising the termination right due to the other party’s unjustified refusal to perform. Furthermore, this does not imply the independent will of either party to steer the contractual relationship towards dissolution; rather, the matter is entrusted to the judiciary to consider the possibility of contract termination, based on the circumstances surrounding each party. From these elements, a clear vision emerges: the termination system has two aspects. First, it is a right for the contracting party who is serious about fulfilling the contract. Second, it is a penalty imposed on those whose actions cause a breach in the performance of the obligations arising from the contractual relationship. To clarify these two concepts, we will present, in turn, the provisions of the termination system, and we pray to God Almighty for success and guidance in this endeavor.